QoS based Admission Control using Multipath Scheduler for IP over Satellite Networks - Lukman Audah; Zhili Sun; Haitham Cruickshank (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents a novel scheduling algorithm to support quality of service (QoS) for multiservice applications over integrated satellite and terrestrial networks using admission control system with multipath selection capabilities. The algorithm exploits the multipath routing paradigm over LEO and GEO satellites constellation in order to achieve optimum end-to-end QoS of the client-server Internet architecture for HTTP web service, file transfer, video streaming and VoIP applications. The proposed multipath scheduler over the satellite networks advocates load balancing technique based on optimum time-bandwidth in order to accommodate the burst of application traffics. The method tries to balance the bandwidth load and queue length on each link over satellite in order to fulfil the optimum QoS level for each traffic type. Each connection of a traffic type will be routed over a link with the least bandwidth load and queue length at current time in order to avoid congestion state. The multipath routing scheduling decision is based on per connection granularity so that packet reordering at the receiver side could be avoided. The performance evaluation of IP over satellites has been carried out using multiple connections, different file sizes and bit-error-rate (BER) variations to measure the packet delay, loss ratio and throughput.